(3GdGhQGb GdeGdjI,GdJCLjQ GdJehjdj,GdGSJKeGQ,GdHfhc , GdJLGQI h GdeDSSGJ GdJLGQjI ,GGdUdM GdhGbj h GdGadGSs - (3dDj(B, (3hOjGfs ((3YeGf(B:s (3OGQ GdeSJbHd(B,s, 2010)
(3bGfhf GdChQGb GdeGdjI bGfhf eDbJ Qbe (B76 (3dSfI (B2002(3, bGfhf GdJCLjQ GdJehjdj bGfhf eDbJ Qbe (B16 (3dSfI (B2002 (3h bGfhf GdGSJKeGQGdeDbJ Qbe (B68 (3dSfI (B2003 (3GdefThQ Ydi GdUaMI (B3238 (3ef YOO GdLQjOI GdQSejI Qbe (B4606 (3JGQjN (B16/6/2003 (3, bGfhf GdHfhc Qbe (B28 (3dSfI (B2000(3UOQ aj YOO GdLQjOI GdQSejI Qbe (B14448 (3BH SfI (B2000(3; bGfhf GdJLGQI Qbe (B12 (3dSfI (B1966s
Keywords: (3GdJLGQI `` bhGfjf h JTQjYGJs; (3GdbGfhf GdJLGQjs